Comparing learning objects for effective learning in Mathematics - Descalço, L. (2020)
The too high number of students per class, situation typically found in higher education in Portugal, makes it difficult to adopt an approach were the student work is taken as the center of the learning process. The use of digital contents in this context is helpful for the students to build their own appropriate environment outside the classroom, using all support and learning material built up for that purpose. A fundamental problem we have in Mathematics is that many students are not well prepared in previous concepts. We have been developing and using several kinds of learning objects (LO) for calculus in the recent years, some of them dedicated to recall previous concepts. Among all kinds of contents, students valorize more learning objects that simultaneously challenge them and give them useful feedback. In this paper, we compare the usefulness of different kinds of LO, using computers, in a calculus course for students from several sciences and engineering, with a population of 290 students, based on a survey answered by 40% of them. The learning objects include multiple-choice questions with detailed solutions, quizzes, formative tests, short videos, and others. We present a quantitative analysis comparing different kinds of LO, considering students of several study areas. Together with the quantitative analysis, we add some qualitative considerations based on student’s answers to open questions concerning the learning methodology adopted.